A Historical Analysis of Critiques in the Talent Management Debate. Issue 3 (July 2019) - Sparrow, Paul
Current debates around talent management echo previous concern about the development of the field of IHRM. This paper uses historical analysis to examine two questions: has the field followed a logical progression and process of increasing coherence; and has its narrative been shaped in ideological ways? It identifies six concepts that guided and enabled the subsequent development of the talent management field. It shows how a selection of these ideas were re-packaged through the introduction of new notions to build two competing narratives: a star performer perspective and a human capital management perspective. It examines the progressive critiques and problems that then had to be solved to address these concerns. There is evidence of periodic ideological re-interpretations of talent management but there has nonetheless been a logical, progressive and issues-driven evolution of ideas in the field into which the current critical perspectives must now be fitted.